Atlas of Ultrasound-Guided Procedures in Interventional Pain Management (Springer New York, 2018)
With a focus on anatomy and sonoantomy, this beautifully illustrated updated edition captures the latest advances in the rapidly growing field of ultrasound-guided pain medicine and MSK procedures. This atlas is divided into seven sections that provide an overview and focus on interventional approaches and advancements. Authored by international experts, each clinical chapter features a maximal number of instructive illustrations and sonograms and provides a description of sonoanatomy, instructions on performing the procedure and how to confirm appropriate needle placement. This book will help encourage and stimulate physicians to master approaches in interventional MSK and pain management.